Knowledge and learning in a service context : sensemaking in an online community of hair stylists : a thesis presented in partial fulfillment of the requirements for the degree of Doctorate of Philosophy in Management at Massey University at Auckland, Albany Campus - Fachira, Ira (Massey University, 2013)
Little research is directly concerned with knowledge and learning in the service context, especially with how frontline service personnel learn to deal with the technical and social aspects of service encounters. This thesis aims to explore knowledge and learning in the service context by investigating how frontline personnel make sense of their workplace experiences in an online community of practice. This thesis uses Goffman‘s (1959) dramaturgical metaphor concepts to look at service encounters as similar to a theatre. Lave and Wenger‘s (1991) situated learning paradigm is used as an interpretive lens to examine learning as the development of practice and identities through participation in a community of practice. This research presents a qualitative study of a single case: an online community of hair stylists called Hair Pro Forum. Data was collected from the Forum‘s online discussions stored in the community‘s archive. Discussion threads are characterised by storytelling and collective interpretation of workplace events. There are two forms of data in this study: discussion strings and stories. The primary data for this study was 31 strings and 29 stories. Data was examined using thematic analysis. Knowledge and learning in the service context was analysed using Weickian (1995) ideas about collective and individual sensemaking activities. Gabriel‘s (1995) notion of =story-work‘ enabled sense to be made of hairstylists‘ sensemaking activities. Results of the study indicated that knowledge in the service context was constructed through narrative sensemaking, conducted online through discussion. Hair stylists created meaning by sharing stories about a service encounter as a specific event, consisting of technical and social interaction approaches suitable for the particular situation.Findings are that the initial stories of the hairstylists are posted as possible interpretations of an event, and this enables the community to respond and make collective sense of the event. Sensemaking activities enable hairstylists to gain deeper understandings of the significance of their actions in light of the flux of events in the workplace. Narrative performance invites collective interpretation, which enables learning, which in turn assists the construction of professional identity. This study provides an exemplar of how sensemaking and storytelling in an online community can help develop learning and professional identity. Further, the study shows how the activity of learning about customers is social, on-going and constantly being interpreted. The study also provides empirical evidence that knowledge about the service encounter is not static but is continuously generated.
Keywords: Hairdressing; Computer network resources; Online social networks; Communities of practice; Knowledge management